1943
DOI: 10.1073/pnas.29.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Some Interrelationships of Pyridoxine, Alanine and Glycine in Their Effect on Certain Lactic Acid Bacteria

Abstract: Various investigators1 2, 3 have shown that pyridoxine (vitamin B6) under certain conditions is a necessary growth factor for certain species of lactic acid bacteria. One such organism is Streptococcus lactis R. In a detailed study of the requirement of this organism for pyridoxine, Snell, et al.,4 showed that there existed in natural products a substance which could be derived from pyridoxine by metabolic processes, which far surpasses pyridoxine in its physiological activity for this organism. To distingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1946
1946
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(26 citation statements)
references
References 3 publications
3
23
0
Order By: Relevance
“…There is the example described by Ford et al (1958) in which Streptococcus bovis exhibited a number of nutritional requirements when cultivated aerobically, although anaerobically the organism grew well in the absence of any added vitamin. The interrelation between pyridoxine and alanine was noted by Snell & Guirard (1943), and Griffin & Racker (1955) showed that the CO, requirement of Neisseria gonorrhoeae could be replaced by hypoxanthine, uracil and oxalacetate. These are only a few of the examples which can be cited; they serve to emphasize the caution which must be exercised.…”
Section: -2mentioning
confidence: 90%
“…There is the example described by Ford et al (1958) in which Streptococcus bovis exhibited a number of nutritional requirements when cultivated aerobically, although anaerobically the organism grew well in the absence of any added vitamin. The interrelation between pyridoxine and alanine was noted by Snell & Guirard (1943), and Griffin & Racker (1955) showed that the CO, requirement of Neisseria gonorrhoeae could be replaced by hypoxanthine, uracil and oxalacetate. These are only a few of the examples which can be cited; they serve to emphasize the caution which must be exercised.…”
Section: -2mentioning
confidence: 90%
“…he inhibition of bacterial growth by glycine is well established (1)(2)(3), and the cell wall is the main target of glycine action (4). Glycine is incorporated instead of alanine into peptidoglycan precursors (5,6), and eventually into peptidoglycan (4).…”
mentioning
confidence: 99%
“…In addition, because glycine-containing peptide units are poor substrates in the transpeptidation reaction, a high percentage of muropeptides are not cross-linked, resulting in severely restricted growth (4). Sensitivity to an excess of glycine has been observed in various bacteria, including Bacillus subtilis, Streptococcus lactis, and Staphylococcus aureus (1,3). However, glycine is the simplest material for protein synthesis, despite its toxic activity.…”
mentioning
confidence: 99%
“…coli by cultivation in the presence of methionine and sulphanilamide supports their conception of the interrelation of methionine and p-aminobenzoic acid in metabolism (Kohn and Harris, 1942). Snell and Guirard (1943) found that alanine in sufficient concentration could completely replace pyridoxin for the growth of Streptococcus lactie; no other amino-acid did this. In the conditions of tho test, glycine and threonine and, at higher concentrations, serinc and p-alanine inhibited growth.…”
Section: Inter-relations Of Metabolites and Anti-metabolitesmentioning
confidence: 97%
“…This inhibition was abolished by pyridoxin but by no other vitamin, and by alanine. Examples of inhibitions by certain amino-acids and their antagonization by other amino-acids, at very low concentrations, were first carefully studied by Gladstone (1939) but, in the case studied by Snell and Guirard (1943), there is the furthcr relation with pyridoxin metabolism. Thus both the examples mentioned here are cases where, presumably, metabolic reactions involving the essential metabolites, p-aminobenzoic acid and pyridoxin, are linked with reactions involving amino-acids.…”
Section: Inter-relations Of Metabolites and Anti-metabolitesmentioning
confidence: 99%